A rare PBX1 variant identified in adulthood: a case report - Han, Ah-Rim; Moon, Youngyoon; Kim, Yang-Gyun; Lee, Sang-Ho; Moon, Ju-Young; Lim, Sung Jig; Lee, Yu Ho; Jung, Su Woong (Frontiers in Medicine, 2025)
Abnormalities in PBX1 represent a monogenic cause of congenital anomalies of the kidney and urinary tract (CAKUT). However, their phenotypic heterogeneity poses a challenge for timely detection, particularly in the absence of overt anomalies in the kidney and urinary tract. Here, we present a 28-year-old male diagnosed with a rare PBX1 nonsense variant identified during the evaluation of early-onset chronic kidney disease. As part of the initial workup for decreased renal function and proteinuria, a kidney biopsy was performed, revealing focal segmental glomerulosclerosis (FSGS) and acute tubular necrosis without an identifiable cause. He was initially treated with renin-angiotensin system inhibitors, followed by glucocorticoid and/or cyclosporine therapy for four years. Despite these interventions, his serum creatinine levels gradually increased without any improvement in proteinuria. Genetic testing, performed seven years after the initial visit, revealed a rare de novo heterozygous PBX1 variant, p.Arg93Ter (c.277C > T), classified as likely pathogenic. Reverse phenotyping identified cryptorchidism and dysmorphic external ears, both of which are extrarenal manifestations commonly associated with PBX1-related CAKUT. Although this variant is predicted to be deleterious, it is flagged as escaping nonsense-mediated decay, which may explain the absence of apparent structural anomalies in the kidneys. PBX1 is prominently expressed in interstitial and endothelial cells in both fetal and adult human kidneys, and its function is not directly implicated in podocyte or tubular cell biology. Therefore, the inadvertent pathological findings in this genetic disorder may be attributed to reduced nephron endowment and/or disturbance in reciprocal cellular interactions. This case broadens the phenotypic spectrum of PBX1-related disorders and highlights its renal manifestations, further expanding the clinical heterogeneity of FSGS.